Strong sustainability and the environmental dimension of the Sustainable Development Goals - Arkaitz Usubiaga-Liaño; Alison Fairbrass; Paul Ekins (Global Sustainability)
Abstract Non-technical summary The Sustainable Development Goals (SDG) are at the core of the development agenda. Despite their wide adoption, it is still unclear the extent to which they can provide insights on environmental sustainability. The paper presents an assessment of the potential of the indicators used in the SDGs to track environmental sustainability. The results show that only a few SDG indicators describe the state of the environment, and those that do so, do not, generally, have science-based targets that describe whether environmental sustainability conditions are met. The latter aspect should be reinforced in framework that will replace the SDGs after 2030.